Dinner or dismay? Altered behavioural response of crayfish to alarm cues when fed a conspecific diet - Gabrielle H. Achtymichuk; Kaitlyn M. Fish; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2025)

Abundance Trends of Pacific Salmon During a Quarter Century of ESA Protection - Michael J. Ford; Steven T. Lindley; Katie A. Barnas; Andrew O. Shelton; Brian C. Spence; Laurie A. Weitkamp; Damon M. Holzer; David A. Boughton; Elizabeth E. Holmes; James M. Myers; Chris E. Jordan; Heidi Fish; et al. (Fish and Fisheries, 2025)
Between 1989 and 2007, 28 Distinct Population Segments (DPS) of Pacific salmon ( Oncorhynchus spp.) spawning in rivers in California and the Pacific Northwest (Oregon, Washington, Idaho) were listed (protected) under the US Endangered Species Act (ESA). In the roughly 25 years since then, considerable efforts have been made to recover these populations, but no DPS has increased sufficiently to be delisted. We evaluated abundance trends of ESA‐listed Pacific salmon DPS, along with DPS that were not ESA‐listed. Our goal was to evaluate whether protected DPS increased in abundance during the period of protection (nominally 1995–2020 in our study), either in absolute terms or relative to the unprotected DPS. A majority of the protected DPS had increasing abundance trends over this time period, and protected populations had higher median trends than non‐protected populations of the same species. Geographically, populations in the Pacific Northwest had higher median trends than those in California. Among species of protected populations, Chinook salmon ( O. tshawytscha ), chum salmon ( O. keta ) and sockeye salmon ( O. nerka ) had higher median trends than coho salmon ( O. kisutch ) and steelhead (anadromous O. mykiss ). For most DPS (listed and unlisted), trends in harvest rates and hatchery releases were relatively stable during the same time period, whereas trends in indicators related to freshwater and marine climate were generally negative for salmon. Our results suggest that salmon recovery actions may have helped to stabilise and increase protected DPS, but most remain far below their recovery goals.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Infralimbic and dorsal raphé microinjection of the 5-HT1B receptor agonist CP-93,129: attenuation of aggressive behavior in CFW male mice - S. Faccidomo; I. M. H. Quadros; A. Takahashi; E. W. Fish; K. A. Miczek (Psychopharmacology, 2012)

Field and climate‐based model for predicting the density of host‐seeking nymphal Ixodes scapularis , an important vector of tick‐borne disease agents in the eastern United States - Maria A. Diuk‐Wasser; Gwenaël Vourc'h; Paul Cislo; Anne Gatewood Hoen; Forrest Melton; Sarah A. Hamer; Michelle Rowland; Roberto Cortinas; Graham J. Hickling; Jean I. Tsao; Alan G. Barbour; Uriel Kitron; et al. (Global Ecology and Biogeography, 2010)
Aim Ixodes scapularis is the most important vector of human tick‐borne pathogens in the United States, which include the agents of Lyme disease, human babesiosis and human anaplasmosis, among others. The density of host‐seeking I. scapularis nymphs is an important component of human risk for acquiring Borrelia burgdorferi , the aetiological agent of Lyme disease. In this study we used climate and field sampling data to generate a predictive map of the density of host‐seeking I. scapularis nymphs that can be used by the public, physicians and public health agencies to assist with the diagnosis and reporting of disease, and to better target disease prevention and control efforts. Location Eastern United States of America. Methods We sampled host‐seeking I. scapularis nymphs in 304 locations uniformly distributed east of the 100th meridian between 2004 and 2006. Between May and September, 1000 m 2 were drag sampled three to six times per site. We developed a zero‐inflated negative binomial model to predict the density of host‐seeking I. scapularis nymphs based on altitude, interpolated weather station and remotely sensed data. Results Variables that had the strongest relationship with nymphal density were altitude, monthly mean vapour pressure deficit and spatial autocorrelation. Forest fragmentation and soil texture were not predictive. The best‐fit model identified two main foci – the north‐east and upper Midwest – and predicted the presence and absence of I. scapularis nymphs with 82% accuracy, with 89% sensitivity and 82% specificity. Areas of concordance and discordance with previous studies were discussed. Areas with high predicted but low observed densities of host‐seeking nymphs were identified as potential expansion fronts. Main conclusions This model is unique in its extensive and unbiased field sampling effort, allowing for an accurate delineation of the density of host‐seeking I. scapularis nymphs, an important component of human risk of infection for B. burgdorferi and other I. scapularis ‐borne pathogens.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Topotecan in the Treatment of Acquired Immunodeficiency Syndrome-Related Progressive Multifocal Leukoencephalopathy - W Royal III; B Dupont; D McGuire; L Chang; K Goodkin; T Ernst; MJ Post; D Fish; G Pailloux; H Poncelet; M Concha; L Apuzzo; et al. (Journal of NeuroVirology, 2003)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Accurate Derivation of Total and Stratospheric Vertical Columns of NO2 from Ground-Based Zenith-Sky Measurements - K. E. Preston; D. J. Fish; H. K. Roscoe; R. L. Jones (Journal of Atmospheric Chemistry, 1998)

Investigating the relaxation, following diazo-2 laser flash photolysis, of a skinned trabecular preparation from SHR hypertrophied left ventricle - E. C. Johns; E. A. M. Hodson; H. Fish; J. S. Lymn; H. Thurston; I. P. Mulligan; C. C. Ashley (Pflügers Archiv - European Journal of Physiology, 1998)